A one-step process for preparing a phenyl-modified g-C3N4 green phosphor with a high quantum yield. Issue 81 (8th November 2017) - Chen, Tianxiang; Chen, Chengcheng; Liu, Qiong; Zhang, Zhengguo; Fang, Xiaoming
Abstract : Herein a simple one-step process for preparing a g-C3 N4 -based green phosphor was presented, which involved thermal polymerization of 2, 4-diamino-6-phenyl-1, 3, 5-triazine under an atmosphere of argon, to prepare phenyl-modified g-C3 N4 . Abstract : Herein a simple one-step process for preparing a g-C3 N4 -based green phosphor was presented, which just involved thermal polymerization of a single precursor, 2, 4-diamino-6-phenyl-1, 3, 5-triazine, under an atmosphere of argon, to prepare phenyl-modified g-C3 N4 . The effects of the annealing temperature and time on the crystalline structure, chemical composition, morphology, optical absorption properties, and photoluminescence emission behavior of the obtained samples were investigated systematically. It was found that the phenyl-modified g-C3 N4 prepared at 400 °C for 40 min exhibits strong green emission with a quantum yield of as high as 38.08%, comparable to those of the g-C3 N4 nanoparticles and quantum dots obtained from the multi-step preparation and post-treatment processes. The emission spectrum of the phenyl-modified g-C3 N4 sample can be fitted into four peaks centered at around 465, 490, 520 and 545 nm, suggesting that the phenyl-modified g-C3 N4 phosphor possesses multi-fluorophores or luminescent species. The introduction of the phenyl groups leads to the decrease in band gap and thus the red shift in emission as compared with pristine g-C3 N4 . The simple preparation process along with high quantum yield make this phenyl-modified g-C3 N4 green phosphor show great potential in practical applications.